Persien in der Mitte des 19. Jahrhunderts: Reiseeindrücke in Arminius Vámbérys Meine Wanderungen und Erlebnisse in Persien (1867) - Ruth Bartholomä (Recherches Germaniques)
In the year 1862, the Hungarian Turcologist Arminius Vámbéry (1832-1913) traveled to Tehran and the South of Iran, publishing a report about this trip five years later in the form of his travelogue with the title My Wandering and Adventures in Persia (German title: Meine Wanderungen und Erlebnisse in Persien, Pest 1867). As Vámbéry traveled not as a Hungarian, but incognito, as an Ottoman dervish with the name Reşid Efendi, his perspective on Shiite Persia is of special interest. At the same time, it is interesting to point out what knowledge about Persia he wanted to transmit to his contemporary European reader and how his report, as well as his person, were received by the readers. Therefore, this paper takes into account Vámbéry’s travelogue, especially the chapters concerning his stay in Isfahan, as well as German-language reviews published shortly after the publication of the book.